(untitled) - Vallance, Elizabeth (Elizabeth M.) (Cambridge [England],New York, NY, USA, 1995)
This book looks at business ethics from the perspective of the business practitioner, but with the rigour of the moral philosopher. Intended for introductory students of business, commerce and management studies, Business Ethics at Work begins by setting business clearly in the context of creating value for its owners, and develops a practical ethical decision model which can be simply and relevantly applied to the hard moral choices with which business people are faced day to day. Against this background, some of the major ethical issues which arise in business are explored, for example, in human resource management, finance, marketing and advertising, the management of the environment and corporate governance. In conclusion the book looks at the nature of ethical audit and argues that for the business of the future, the identification of its ethical values and their integration into its policies and practices will be a crucial ingredient of success.
Kinh doanh quốc tế nâng cao
Keywords: Business ethics,Management,Đạo đức kinh doanh,Quản lý; Moral and ethical aspects,Khía cạnh luân thường và đạo đức